Beyond Reading Difficulties: Differences in Oral Language in Children with Dyslexia, Reading Difficulties, and Typical Development - Verdaguer-Ribas, Oriol; Giberga, Albert; Ahufinger, Nadia; Aguilera, Mari (Revista de Investigación en Logopedia, 2025)
Oral language and reading are interdependent skills essential for cognitive and academic development. Although phonological awareness has been the most extensively studied component of oral language in dyslexia, recent research highlights the importance of other components such as vocabulary, grammatical comprehension, and communicative skills. This study has two main objectives: (1) to compare these skills among three groups—children with dyslexia, children with reading difficulties, and typically developing children, and (2) to analyze the predictive capacity of these three components of oral language in relation to reading efficiency, accuracy, and speed. The results indicate that the dyslexia group exhibits greater difficulties in grammatical comprehension and communicative skills compared to the other groups. Additionally, the group with reading difficulties tends to perform lower in these components than the typically developing group. Furthermore, vocabulary level significantly predicts reading efficiency, while grammatical comprehension significantly predicts word reading accuracy. None of the three components significantly predict either word or pseudoword reading speed, nor pseudoword accuracy. These findings underscore the importance of a multidimensional assessment of oral language in children with reading difficulties and suggest the need for broader interventions that address both phonological aspects and other linguistic components.